Seasonal Variations of Phytochemical Content and Antioxidant Activity of Senna italica Leaves - C. Mncube, Sibusiso; S. Gololo, Sechene; A. Mogale, Motetelo (Asian Journal of Chemistry, 2020)
Senna italica is a widely used medicinal plant well known for their laxative properties and high antioxidant activity, as well as possession of a variety of bioactive compounds. For its optimum usage, the current study was aimed at the determination of seasonal variations in the phytochemical content and antioxidant activity of its leaves. The leaves of Senna italica were collected during each of the four seasons (autumn, winter, spring, summer) in the year 2018. Total phenolic, total tannin, total flavonoid and total saponin contents of the leaves were determined using UV spectrophotometric method. Antioxidant activity was evaluated using the DPPH free radical scavenging activity and H2O2 reducing activity assays. Total phenolic content was recorded in higher amounts during autumn; total tannin content was in higher amounts during autumn and summer; total flavonoids were higher during autumn and summer and total saponins were higher in summer. High antioxidant activity strength demonstrated through relatively lower IC50 was shown in summer and autumn which, was consistent with the relative phytochemical contents. The current results suggest that the optimum period of harvest for maximum benefit regarding the antioxidant activity of Senna italica leaves is between summer and autumn and that its antioxidant activity strength is aligned to the accumulation of the antioxidant compounds.